The Impact of Pollution on Children’s Health: A Call for Global Accountability and Enforcement - Kharytonov, Mykola M.; Hernandez, Anne P.; Vasylyeva, Tetyana L. (International Journal of Child Health and Nutrition, 2013)
Environmental pollution in large industrial centers has had a negative impact on the population’s health, specifically among children. Our objective is to provide a systematic review of the literature, focusing on the impact of environmental pollutants from urban and metropolitan areas on pediatric health. Disregard for the Earth’s atmosphere can negatively impact our fragile ecosystem and create a global toxicity. The impact of industrial growth and economic development has become paramount to modern society. Unfortunately, future generations will pay the consequences of the world’s failure to implement regulations to secure a safe environment for our children’s health and development. Pollutants penetrate an organism through different routes and change physiological processes, which leads to a decrease in microbial resistance by weakening the child’s immune system. The major contaminants are: polycyclic aromatic hydrocarbons, lead, manganese, sulfur dioxide, airborne fine particles, and nitrogen dioxide. Xenobiotics negatively affect the morphological, functional, biochemical parameters, genetics, and epigenetics of the body. It is well documented that the physical development and psychological well-being of children is adversely affected by pollution. The accumulation of heavy metals and other contaminants adversely affected a child’s health has been found in the pediatric population. An effort has been made to develop detoxicant remedies, in particular, some enterosorbents and natural adaptogens. Research is ongoing to improve medical rehabilitation of children, who already are affected. Public education and regulations regarding emerging non-pollutant industrial technologies is called for. A global system of accountability and enforcement regarding environmental protection needs to be implemented.